If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = -7(2 + -1x) 35 = (2 * -7 + -1x * -7) 35 = (-14 + 7x) Solving 35 = -14 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 35 + -7x = -14 + 7x + -7x Combine like terms: 7x + -7x = 0 35 + -7x = -14 + 0 35 + -7x = -14 Add '-35' to each side of the equation. 35 + -35 + -7x = -14 + -35 Combine like terms: 35 + -35 = 0 0 + -7x = -14 + -35 -7x = -14 + -35 Combine like terms: -14 + -35 = -49 -7x = -49 Divide each side by '-7'. x = 7 Simplifying x = 7
| 2x(5)=21 | | uw+uv=r | | 3x^2+10x-11=3-9x | | 6x-3-6x-8=11x | | 10-2(a+2)=9+a | | 45x^2-42x^3-24x^4=0 | | (x+4)+=-21 | | 2t-11=-4t+1 | | 4w-6=14 | | 20x^3+33x^2+7x= | | .20x+.50=1 | | -4(y-4)=-4y+8 | | -7(x-5)+2=37 | | 2n+7n=63 | | 4(2r+1)-3(2r-5)=40 | | 6-6x+8+3x+4x-3=5+3(4) | | 16+3=10x-5 | | 2d+3=4(d-1) | | -10(b-3)=100 | | 0.5+6=36 | | 28x^3-6x^2-4x=0 | | 3/4(z-1/9)=1/9(z-1/8) | | -10x=2+10x-8+1 | | 5x^2-9x-18= | | 8(4)-4(4-2)=24 | | q=4h+4z | | 8+7n=9.5-4n | | -4(m+5)+2m=3(m+2) | | (4-z)(-1)= | | (-8)+6= | | 32-8j=4(j-4) | | (4+x)2= |